Repressed Catholic Priests and Monks during the First Years of the Occupation and Annexation of the Republic of Lithuania: June 1940–June 1941 - Grickevičius, Artūras (Genocidas ir rezistencija, 2019)
The subject investigated has not been systematically researched at scientific level until now. The claims made by historians and other authors are fragmented and controversial. However, the publications of historical sources necessary for the subject under research, particularly Volume 1 of the list of names published by the Genocide and Resistance Research Centre of Lithuania, as well as numerous archival documents make it possible to reveal the main features of the reprisals of Lithuanian priests and monastic communities in 1940 and 1941. During the occupation and annexation of the Republic of Lithuania, local Catholic priests, monks and nuns were not among the most important groups of the repressed, i.e. among politicians, white collar workers, officers and public figures. Nevertheless, the registration and surveillance of priests, the cases of the annihilation especially of the Russian Orthodox Church and smaller religious groups of the aggressor country, testify indirectly to the fact that the oppressive apparatus of the Empire that was hostile to religion was getting ready to annihilate the Lithuanian Catholic priests at least as a separate group. The NKVD / NKGB took efforts to win over as many priests as possible. About 115 priests (7.9% of all the priests) were repeatedly summoned to the agencies with this purpose in mind but the result was as poor: 12 of those who promised to arrive (0.8% of all priests, 10.4% of recruited priests), three of them staff workers (0.2% of all priests, 2.6% of recruited priests) showed up. According to the available research results, during the period examined a total number of repressed Catholic priests and monks in Lithuania (of the local Church Province, the part of the Roman Catholic Metropolitan Archdiocese of Vilnius assigned to Lithuania, and Polish refugees) is about 111 persons: 64 (almost 58%) Lithuanian and 47 (over 42%) Polish. From the Lithuanian Church Province or its monasteries and convents 61 persons were repressed, out of whom 53 were diocesan priests, five were monks ordained as priests, three were from monastic communities (one brother and two sisters): 21 from Kaunas diocese, 19 from Vilkaviškis diocese, 11 from Panevėžys diocese, and five from Kaišiadorys and Telšiai dioceses each; all of them were Lithuanians. From the Lithuanian part of the Roman Catholic Metropolitan Archdiocese of Vilnius and the monastic communities based there, about 15 priests (three Lithuanian and 12 Polish) were subject to repression; fewer than half of them were priests, the others were nuns. Taking together the instances in the parts of the Metropolitan Archdiocese of Belarus and Poland, based on the facts from a longer period (from September 1939 until July 1941), the number of the repressed priests in the archdiocese is at least 62 persons: 34 were refugees who suffered from repression; about 27 of them were nuns. The number of people who suffered greatly, i.e. were imprisoned and exiled before Hitler’s war against the “Bolsheviks” were at least 57 Lithuanian Catholic priests and monks (from the local ecclesiastical province and the part of the Roman Catholic Metropolitan Archdiocese of Vilnius). The number of Lithuanian priests – 17 – who were killed by the retreating Soviet Army troops at the first stage of the war between Nazi Germany and the USSR that has been known for a long time remains the same. Nevertheless, counting the priests killed not only in the Lithuanian Church Province and in the part of the Vilnius Archdiocese that belonged to Lithuania but also analogous facts from the parts that belonged to Belarus and Poland, the number of the victims of this category amounts to at least 26. The war that broke out between Hitler and Stalin opened the road to freedom for some priests and members of the monastic community. Between 16 and 18 priests were liberated or freed themselves from prisons in Lithuania, while most of Polish priests who were taken to forced labour camps or exiled were granted an amnesty; later they joined Polish army units and became chaplains. The number of arrested, imprisoned, taken to forced labour camps and exiled priests and members of monastic communities is much higher than those who promised to collaborate with the KGB and joined the staff, which demonstrates that the Lithuanian clergy as well as those who arrived from Poland avoided collaborating with the occupying powers; almost all of them resisted, did not succumb to this temptation and did not act under compulsion.